The role of exosomes in liver cancer: comprehensive insights from biological function to therapeutic applications - Zhang, Yinghui; Zhang, Congcong; Wu, Nan; Feng, Yuan; Wang, Jiayi; Ma, Liangliang; Chen, Yulong (Frontiers in Immunology, 2024)
In recent years, cancer, especially primary liver cancer (including hepatocellular carcinoma and intrahepatic cholangiocarcinoma), has posed a serious threat to human health. In the field of liver cancer, exosomes play an important role in liver cancer initiation, metastasis and interaction with the tumor microenvironment. Exosomes are a class of nanoscale extracellular vesicles (EVs)secreted by most cells and rich in bioactive molecules, including RNA, proteins and lipids, that mediate intercellular communication during physiological and pathological processes. This review reviews the multiple roles of exosomes in liver cancer, including the initiation, progression, and metastasis of liver cancer, as well as their effects on angiogenesis, epithelial-mesenchymal transformation (EMT), immune evasion, and drug resistance. Exosomes have great potential as biomarkers for liver cancer diagnosis and prognosis because they carry specific molecular markers that facilitate early detection and evaluation of treatment outcomes. In addition, exosomes, as a new type of drug delivery vector, have unique advantages in the targeted therapy of liver cancer and provide a new strategy for the treatment of liver cancer. The challenges and prospects of exosome-based immunotherapy in the treatment of liver cancer were also discussed. However, challenges such as the standardization of isolation techniques and the scalability of therapeutic applications remain significant hurdles.